Pregnancy-related Cardiovascular Deaths in California: Beyond Peripartum Cardiomyopathy. Issue 3 (September 2016) - Hameed, A.B.; Lawton, E.S.; McCain, C.L.; Morton, C.H.; Mitchell, C.; Main, E.K.; Foster, E.
Abstract : ( Am J Obstet Gynecol. 2015;213(3):379.e1–e10) Cardiovascular disease is currently understood to be the leading cause of pregnancy-related mortality in the United States. The authors of this study analyzed the incidence as well as the type of cardiovascular disease that results in maternal death. Other objectives included analysis of risk factors, including race, ethnicity, and socioeconomic status, as well as birth outcomes, timing and causes of deaths, and symptoms of cardiovascular disease.